The influence of board characteristics on financially distressed companies listed in main market Bursa Malaysia / Syazana Zafirah Saharuddin - Saharuddin, Syazana Zafirah (2019)
Companies may fall into financial distress due to a poor corporate governance such as poor management, lack of directors’ independence, poor leadership structure and incompetent directors. However, companies with good board characteristics may avoid the companies to fall into this financial distress situation. Prior studies had given mixed results on the board characteristics influence on financially distress companies. Thus, this study examined the influence of board characteristics on financially distressed companies listed in the Main Market of Bursa Malaysia. Board characteristics used in this study comprised of board independence, CEO Duality and Audit Committee members’ financial and industry expertise. The total sample data of 46 financial distress and 46 non-financially distress companies were collected from year 2013 until 2016 from Bursa Malaysia website. All data are taken to examine the influence of board characteristics with financial distress companies listed in Main Market of Bursa Malaysia. Binary logistic regression was used to test the relationship between each of board characteristics with financially distressed companies. The result of this study found that CEO Duality and Audit Committee members’ financial and industry expertise had negatively significant with financial distress companies. Meanwhile, board independence is not significant with financial distress companies. This study also found that board characteristics do have significant relationship with financially distressed companies listed in the Main Market of Bursa Malaysia. In addition, the findings of this study will contribute to the limited research regarding the influence of board characteristics on financially distressed listed companies, specifically in the context of Malaysia. Besides that, this study would also be useful for listed issuer and investors, in ensuring the companies have a sound governance through the good board characteristics. So that companies will not fall into financial distress situation.